Pengaruh financial technology adoption capability dan financial literacy terhadap business sustainability - Olvia Intan Permata Sari; Agus Zainul Arifin (Universitas Tarumanagara, 2023)
National economic development is significantly influenced by the existence of MSMEs, as existing economic businesses in Indonesia are dominated by MSMEs. During the Covid-19 pandemic, SMEs faced several challenges to continue their business, not to mention a few business units that had to cease operations. The ability to adapt is an opportunity for the SME sector to improve their strategies, one of which is capital and payment transactions. In this digital age, financial technology (fintech) becomes an alternative in obtaining loans that can help SME business development, especially in terms of financing. Nevertheless, in line with the use of fintech, financial literacy is also required to be improved in order for SMEs to be more prudent in choosing and maintaining access to help finance their business. In addition, by understanding financial literacy, it is hoped that SMEs will be capable of using and managing their financial resources. Through this study, the relation between Financial Technology Adoption Capability and Financial Literacy against Business Sustainability is thoroughly examined and evaluated using the Technology Acceptance Model and the Diffusion of Innovation Theory approach, involving a collection of 149 respondents as the source of data. The result obtained in this study is that financial technology adoption capability and financial literacy have a positive influence on business sustainability. embangunan ekonomi nasional secara signifikan dipengaruhi oleh keberadaan UMKM, hal ini dikarenakan usaha yang ada di Indonesia didominasi oleh UMKM. Pelaku UKM menghadapi beberapa tantangan untuk melanjutkan usahanya, bahkan tidak sedikit unit usaha yang harus berhenti beroperasi di masa pandemi Covid-19. Kemampuan untuk beradaptasi merupakan kesempatan bagi sektor UKM untuk memperbaiki strategi, salah satunya ialah permodalan dan transaksi pembayaran. Pada era digitalisasi, teknologi finansial (tekfin) merupakan salah satu alternatif dalam mendapatkan pinjaman yang dapat membantu perkembangan bisnis UKM, terutama dalam sisi pembiayaan. Namun sejalan dengan penggunaan tekfin, literasi keuangan juga harus ditingkatkan agar pelaku UKM cermat dalam memilih dan menggunakan akses keuangan untuk membantu bisnisnya. Selain itu dengan memahami literasi keuangan diharapkan UKM akan mampu menggunakan dan mengelola sumber daya keuangan yang dimiliki. Penelitian ini memiliki tujuan untuk mengetahui bagaimana pengaruh financial technology adoption capability dan financial literacy terhadap business sustainability dengan metode analisa deskriptif menggunakan pengumpulan responden sebanyak 149 responden. Hasil yang diperoleh dalam penelitian ini adalah financial technology adoption capability dan financial literacy berpengaruh terhadap business sustainability.